Teacher and Learner’s Perceptions on Using Peer Evaluation to Improve EFL Writing The Case of Second year LMD Students at M’sila University - Ines BENSEID, Zineb BOUMEZBEUR (My University, 2020)
Though writing is one of the most required skills at University, it is a challenging task for EFL students. The present conduct investigates teachers’ and learners’ perspectives on implementing peer feedback to boost the writing skill. To conduct this study, the mixed approach was adopted. To support this approach, a questionnaire, an interview, and classroom observation were used to collect data. The analysis of data demonstrates that, both, teachers and learners have positive attitudes towards the use of peer feedback in the writing classroom. In addition to students’ writing improvement, peer feedback helps them to develop autonomy and critical thinking. Moreover, the findings reveal that students have preferences towards written anonymous feedback. The fulfilment of the study was hoped to contrast teachers’ and learners’ perceptions to adjust class instructions to students’ needs and preferences for better achievement.
Keywords: Key words: peer feedback, feedback, teaching writing, EFL learners and teachers.